2022
DOI: 10.3390/ma15030884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sb and Zn Addition on the Microstructures and Tensile Properties of Sn–Bi-Based Alloys

Abstract: The tensile behavior of Sn–Bi–Cu and Sn–Bi–Ni alloys has been widely investigated. Reportedly, the addition of small amounts of a third element can refine the microstructures of the eutectic Sn-58mass% Bi solder and improve its ductility. However, the superplasticity mechanism of Sn-based alloys has not been clearly established. Therefore, in this study, the effects of Sb and Zn addition on the microstructures and tensile properties of Sn–Bi-based alloys were investigated. The alloys were subjected to tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These metals include indium (In, mp: 156.6 • C), tin (Sn, mp: 231.9 • C), and bismuth (Bi, mp: 271.4 • C), all of which melt below 330 • C. Currently, the most commonly used Ga-based LM alloys are eutectic galliumindium alloys (EGaIn, 75% Ga and 25% In by weight, mp: 15.5 • C) and gallium-indium-tin alloys (typically, Galinstan, 68% Ga, 22% In and 10% Sn by weight, mp: 10 • C) [45]. Additionally, some Bi-based alloys can regulate their physical properties by adding different metals, such as the melting point [46,47]. In this review, the term LMs specifically refers to metal Ga and Ga-based LM alloys unless otherwise specified.…”
Section: The Category Of Lmsmentioning
confidence: 99%
“…These metals include indium (In, mp: 156.6 • C), tin (Sn, mp: 231.9 • C), and bismuth (Bi, mp: 271.4 • C), all of which melt below 330 • C. Currently, the most commonly used Ga-based LM alloys are eutectic galliumindium alloys (EGaIn, 75% Ga and 25% In by weight, mp: 15.5 • C) and gallium-indium-tin alloys (typically, Galinstan, 68% Ga, 22% In and 10% Sn by weight, mp: 10 • C) [45]. Additionally, some Bi-based alloys can regulate their physical properties by adding different metals, such as the melting point [46,47]. In this review, the term LMs specifically refers to metal Ga and Ga-based LM alloys unless otherwise specified.…”
Section: The Category Of Lmsmentioning
confidence: 99%
“…Rodney, for instance, incorporated 0 to 8 wt.% Sb into Sn, generating whisker-like SbSn precipitates and thereby reducing the creep rate of a Sn solder at 150 • C [11]. Furthermore, Sb could refine the microstructure of Sn-based solders [12,13]. Adding Sb to a SnBi solder improved the shear strength and creep resistance of solder joints [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of alloying elements with minor amounts in Sn-Bi solders could refine the microstructure and improve their mechanical strength [17][18][19][20][21][22][23][24][25][26][27][28][29]. The Sn-Bi-Ag ternary alloys were fabricated and the Bi-rich phase was remarkably refined and uniformly dispersed in the matrix with the addition of 1.0 wt% Ag [19].…”
mentioning
confidence: 99%
“…Yang et al [23] reported that doping with Ni could effectively inhibit the growth of IMC layer between the Sn-Bi solder and the Cu substrate, maintaining the strength of the solder as a result. The effects of other elements such as Sb, In, Zn on the Bi-rich phase formation were investigated [24][25][26][27][28][29]. The results show that the Bi coarsening has been eliminated and the microstructure has been refined with a certain amount of these elements.…”
mentioning
confidence: 99%